The Use of Diglossia in Sumenep Regency, Madura - Naila Wildatis Shofyah (Journal of English Language Teaching and English Linguistics, 2021)
The aim of this research is to find out how disglossia is used in Sumenep Regency, Madura and how its implementation in society. This research is descriptive qualitative by using collecting data technique of interview between the source and the researcher. The result of this research shows that the use of variety of diglossia used in Sumenep is divided into three; there are high, middle, and low variety. High variety of diglossia is used to speak to people with a higher social status. The middle variety of diglossia is used to speak between the older to the younger, and the low variety diglossia is used to speak between friends. Besides, the use high variety of diglossia is mostly applied in the government, and religious activity while middle, and low variety are mostly applied in family, friendship, and selling and buying activity as more higher status people, then the use variety of language used will be higher